Theoretical Foundations, Research of Toponyms - Mirboyeva Kibriyo (Research Parks Publishing LLC, 2024)
Among the numerous problems that linguists are working to solve, a special place is occupied by the study of onomastic vocabulary, namely the toponymy of a particular country or its separate region. This is due, first of all, to the peculiarities of this class of vocabulary, since geographical names, in addition to performing the address-index function, also contain additional information concerning the historical past of the people, their culture, the history of the language, its lexical composition and ways to replenish it.